2021
DOI: 10.3390/ijerph182010622
|View full text |Cite
|
Sign up to set email alerts
|

The Țigani Community Adaptability to Changes in Rural Romania and the COVID-19 Impact

Abstract: Romanian rural villages are struggling to survive present times when youngsters leave for a better life in the city while elders work the land like a hundred years ago. Our paper integrates human environments research with public health preparedness, presenting the Țigani (Gypsy/Roma) ethnic group from rural Romania as an example to the world. The future security of mankind will require a new understanding of the human place in its environment. That will lead to a new society, not the most powerful or intellig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This discrimination, we found, is often linked to the characterisation of the Roma as traditional and culturally conservative. This narrative has been found in different literatures (Tesfay 2009;Voda et al 2021;Woodcock 2007). However, in our study we have found that this is not the case, and that, in fact, we cannot talk about health experiences in Roma communities without considering a multi-dimensional approach that understands that the latter are in fact heterogeneous (Orton et al 2019).…”
Section: Discussionmentioning
confidence: 45%
“…This discrimination, we found, is often linked to the characterisation of the Roma as traditional and culturally conservative. This narrative has been found in different literatures (Tesfay 2009;Voda et al 2021;Woodcock 2007). However, in our study we have found that this is not the case, and that, in fact, we cannot talk about health experiences in Roma communities without considering a multi-dimensional approach that understands that the latter are in fact heterogeneous (Orton et al 2019).…”
Section: Discussionmentioning
confidence: 45%
“…Due to the importance of maintaining a healthy gut and a balanced microbiome, the therapeutic approach of UTI could be oriented, at least concurrently with the antibiogram, towards microbiome testing and management. Both patients and general practitioners must understand the need to reconsider the management of UTI recurrences, to adapt [ 49 , 50 , 51 , 52 ] to new long-term therapeutic perspectives and the inclusion of an integrative approach to this problem through interventions aimed at supporting the microbiome, both for otherwise healthy individuals and for vulnerable ones, in which antibiotic treatment also involves other potential risks, such as the case of women during pregnancy [ 53 ]. Microbiota homeostasis and the treatment of obesity and related comorbidities may benefit from gut microbiome manipulation through dietary modifications, lifestyle adjustments, prebiotics, and probiotics [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was also demonstrated in the Tigani community in rural Romania where intense social cooperation, strong sense of family, community and mutual assistance helped them to fight COVID-19. It also strengthened adaptability to the societal changes and their power to keep intact their cultural identity [206]. Grassroots organizations in the Andes instituted a range of hybrid reciprocity practices as essential for provisioning during COVID-19.…”
Section: Role Of Digital Technologymentioning
confidence: 99%